A polymorph of tetraethylammonium chloride - Yan, Yong (International Union of Crystallography, 2009)
The structure of the title compound, C(8)H(20)N(+)·Cl(−), is compared with a polymorph that was described earlier in the same space group. Differences in the conformations of the ethyl groups of the cation exist between the polymorphs. This study is given here in order to provide additional unit-cell data for use in qualitative identification of crystalline samples obtained in syntheses in which Et(4)N(+)·Cl(−) is either used or generated.